2022
DOI: 10.3389/fpls.2022.793644
|View full text |Cite
|
Sign up to set email alerts
|

Partially Resistant Avocado Rootstock Dusa® Shows Prolonged Upregulation of Nucleotide Binding-Leucine Rich Repeat Genes in Response to Phytophthora cinnamomi Infection

Abstract: Avocado is an important agricultural food crop in many countries worldwide. Phytophthora cinnamomi, a hemibiotrophic oomycete, remains one of the most devastating pathogens within the avocado industry, as it is near impossible to eradicate from areas where the pathogen is present. A key aspect to Phytophthora root rot disease management is the use of avocado rootstocks partially resistant to P. cinnamomi, which demonstrates an increased immune response following infection. In plant species, Nucleotide binding-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…In plants, the largest group of R proteins are that of cytoplasmic nucleotide-binding leucinerich repeat (NLR) proteins (McDowell and Woffenden, 2003). Notably, the full complement of avocado NLRs was recently described using some of the RNA-seq data presented in this study (Fick et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…In plants, the largest group of R proteins are that of cytoplasmic nucleotide-binding leucinerich repeat (NLR) proteins (McDowell and Woffenden, 2003). Notably, the full complement of avocado NLRs was recently described using some of the RNA-seq data presented in this study (Fick et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…The expression patterns for these three major TF families may indicate that the susceptible R0.12 is slowly shutting down biotrophic‐related immune responses at 12 and 24 hpi, while these responses remain activated in the partially resistant Dusa at 24 hpi. Furthermore, these expression patterns may explain the differences in callose deposition, PRR and NLR expression patterns previously observed within resistant and susceptible rootstocks following P. cinnamomi infection (Backer et al., 2022 ; Fick, Swart, Backer, et al., 2022 ; van den Berg et al., 2018 ). Because plant–pathogen interactions are extremely complex, the cause of these observations can only be hypothesized.…”
Section: Discussionmentioning
confidence: 93%
“…The increased expression of PaMYB and PaWRKY genes, which group closely with defence-related AtMYBs and WRKYs, at 120 hpi were unexpected as these defence-related TFs often activate the expression of many PRR and NLR genes. Previous studies reported increased expression levels of most PaPRRs and PaNLRs at 6, 12 and 24 hpi in Dusa and R0.12 (Backer et al, 2022;Fick, Swart, Backer, et al, 2022). Thus, it was expected that a higher number of defence-associated PaMYBs and PaWRKYs would be expressed at these early time points.…”
Section: The Expression Patterns For Pamyb and Pawrky Tfs Clearlymentioning
confidence: 89%
See 1 more Smart Citation
“…For example, 22 NLRs were upregulated in Raphanus sativus resistant to Plasmodiophora brassicae , but not in a susceptible genotype during P. brassicae infection ( Wang et al, 2022a ). Furthermore, significant differences in NLR expression were observed between a partially resistant and susceptible Persea americana rootstocks infected with Phytophthora cinnamomi , especially after 6 h post-inoculation ( Fick et al, 2022 ). The expression of NLR genes is regulated by three main mechanisms: (1) epigenetic mechanisms, (2) cis elements and TFs, and (3) post-transcriptional modifications ( Figure 2 ; Bezerra-Neto et al, 2020 ).…”
Section: More Is Better—sometimes: Nlr Expressionmentioning
confidence: 99%